(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ayurveda is a holistic system of medicine. Ayurveda Prescribed many a number of treatment modalities like Shodana and Shamana. Keeping in view of severity of Dosa, Dhatu and Mala vitiation. Among these Snehana and Swedanda are prime with respect to Shodana therapies. Sweda acts as both primary therapy and adjuvant/secondary therapy as per the need of the Rogi, Roga Avastha and Upashaya. The process by which relieves Stambha (rigidity), Gourava (heaviness), Shita (cold) and produces sweating is called Swedana. Acharya Sushruta and Vagbhata have explained 4 varieties of Swedana karma– Tapa, Upanaha, Ushma and Drava sweda. Pariseka is one variety of Drava sweda in which medicated liquid (oil, milk, Takra, Ghrita, Kvatha) filled into pot, jug with spout, or a tube and poured slowly and steadily over the affected part of the body or whole body. An effort has been made to highlight the importance of Parisheka sweda in Urdwajaturgata rogas. Diseases like Vataja abhishyanda and Adhimantha, Arjuna, Karnashula, Shankaka etc.